Characterization of hen phosvitin in aqueous salt solutions: Size, structure, and aggregation. (August 2022) - Takeuchi, Machi; Mashima, Tsuyoshi; Sztucki, Michael; Petukhov, Andrei V.; Vis, Mark; Friedrich, Heiner; Tuinier, Remco
Abstract: Phosvitins is a key egg yolk protein and can often be found in food emulsions. It is highly phosphorylated and hence phosvitins contain a large number of negatively charged amino acid groups, for pH > pI. Due to the presence of these phophoserines, phosvitins bind to positively charged multivalent ions. Its amphipolar structure makes phosvitin also an efficient emulsion stabilizer. The ion binding and emulsifying abilities of phosvitins are influenced by environmental conditions such as pH and ionic strength. Various physicochemical properties of phosvitins such as size and charge under various conditions, and how they self-assemble via multivalent ions are not well-understood. To gain more insight into these physical characteristics, we performed high brilliance synchrotron small angle X-ray scattering (SAXS) on phosvitin solutions. The structure factor S ( q ) obtained from the SAXS profiles showed that the double layer interactions between charged phosvitin assemblies are strongly affected by pH and ionic strength of the buffer. The effects of multivalent ions (Mg 2+, Fe 3+ ) on the size and structure of phosvitin were also investigated. Our results revealed that the aggregation of phosvitin mediated by metal ions is induced by electrostatic attraction and only occurs beyond a threshold cation concentration, where phosvitin loses long-range electrostatic double layer repulsions. These findings help understanding the effects of metal ions and pH on phosvitin in more complex environments such as food emulsions. Graphical abstract: Image 1 Highlights: The physicochemical properties of phosvitins such as size and charge were measured using scattering. An improved purification method was developed to prepare high-purity phosvitins. SAXS yielded the structure factor S ( q ), showing phosvitins behave as charged colloidal spheres. Adding multivalent cations can induce aggregation of phosvitins. A threshold cation concentration is needed to initiate phosvitin aggregation.